Implementasi Perencanaan Kualitas Pendidikan dan Produktivitas Kerja Dalam Meningkatkan Kinerja Dinas Pendidikan Kabupaten Sumedang - Paroli . (STIE AMKOP, 2023)
This study aims to determine the achievement of the implementation of education quality planning and work productivity in improving the performance of the Sumedang Regency Education Office through eight National Education Standards. Based on accreditation data and barriers to achieving National Education Standards for primary and secondary education, Early Childhood Education and Community Education. This research uses descriptive qualitative. Data were obtained from school principals, school supervisors, and the Education Office, and based on purposive sampling of elementary schools in the urban area of Sumedang Regency. Secondary data was obtained from interviews while primary data was obtained from the implementation of eight national education standards. Based on the results of the research, it shows that there are three educational standards that still need attention, namely the standards of educators and educational staff, standards of facilities and infrastructure and graduate competency standards. Obstacles encountered in fulfilling standards at the level of educational units are mainly the standards of educators and education staff, standards of facilities and infrastructure and standards of financing. Thus, not all educational standards have been met by schools. Efforts that need to be made in achieving national education standards are that it is necessary to carry out continuous coaching of schools and school principals. For fulfilling the standards of educators and education staff, facilities and infrastructure standards and financing standards, those who are responsible for fulfilling them are the central government and local governments through education financing policies. Keywords: Implementation of planning, quality of education, work productivity, performance